Analysis of the Effect of Financial Inclusion on the Success of MSME Business Rujak Traders in Natsepa Beach, Central Maluku Regency, Moderated by Fintech - Steven Siaila; Agnes Soukotta; Anna F. de Fretes (PT Mattawang Mediatama Solution, 2023)
This paper aims to test whether financial inclusion affects the success of the business of rojak merchant MSMEs in Natsepa Beach, Central Maluku Regency? Does Fintech affect the success of the business of rojak merchant MSMEs in Natsepa Beach? Does financial inclusion affect the success of the business of rojak merchant MSMEs in Natsepa Beach, Central Maluku Regency with Financial Technology as moderation? The samples taken were all rojak traders located at the location of Natsepa beach; The analysis technique used is path analysis (Path Analysis) The results showed that Financial Inclusion had a positive and significant effect on the success of the rojak trader business in Natsepa Beach, Central Maluku Regency. Financial Technology (FINTECH) does not have a significant effect on the success of the rojak trader business on Natsepa beach, Central Maluku Regency. Financial Inclusion does not have a significant effect on the business success of rojak traders on Natsepa beach, Central Maluku Regency, mediated by FINTECH.